Dinamika parameter kualitas air di Sentra Akuakultur Danau Tondano pada dekade 2010-an - Siahaan, Wira D.; Salindeho, Indra R. N.; Tumembouw, Sipriana S. (e-Journal BUDIDAYA PERAIRAN, 2021)
The objective of this research was to find out the dynamic of  the water quality parameters in Tondano lake aquacultural centres from 2010 to 2019.  Data were collected from scientific information,  either published or unpublished articles, and from the technical reports released by government or non government organization.   Data were tabulated and presented in histogram, scatter and line-diagram and then were compared to the water quality parameters standard according to the Indonesian Government Regulation  No. 82, year 2001.   Data, were then analyzed in the  regression and  correlation analysis,  to  assess the fluctuation trend of the water quality parameters  during 10 years time.  The results show that, in ten years time, the dynamic of the water quality parameters of Tondano Lake waters were as follow:  temperature was in the range of 23-29,9°C, and there was no significant  trend of  fluctuation; water brightness was in the range of 1,1 – 3,15m, and there was a significant trend of decreasing (y = -0.0303x + 63.42 and R² = 0.7501);  pH was in the range of  6,7 – 8,3, and there was an increasing trend but not significant;   DO was in the range of   4,2 – 8,81 ppm, and there was a significant trend of decreasing (y = -0.2868x + 584,22, and  R² = 0.6156);  NH3 was in the range of  0 – 0,77 ppm, and there was a significant  polynomial trend (y = 0.0161x2- 64.726x + 65199 and R² = 0.9737); NO2 was in the range of  0 – 0,09 ppm, and there was a significant polynomial  trend (y = 0.0037x2 - 14.746x + 14859 and R² = 1);  NO3 was in the range of  0 – 1,56 ppm, and there was a significant polynomial trend (y = 0.0436x2 - 175.64x + 176837 and R² = 0.9943);  PO4 was in the range of  0 – 0,37 ppm, and there was a significant polynomial trend (y = 0.012x2 - 48.221x + 48572 and R² = 0.9009).  In general, even though there were significant trends of fluctuation, all the water quality parameters were in the suitable level for aquaculture activities